PENGEMBANGAN MEDIA PLAY MATHEMATICS UNTUK MENGEKSPLORASI PEMAHAMAN KONSEP MATEMATIS DENGAN BERBANTUAN APLIKASI ARTICULATE STORYLINE 3 - Rifa Maulia Sadiah; Depi Setialesmana; Sinta Verawati Dewi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
This study investigates the feasibility and practicality of developing the Play Mathematics media using Articulate Storyline 3, designed to help eighth-grade students at SMP Negeri 6 Tasikmalaya explore their understanding of algebraic concepts. This R&D research employed the ADDIE model and involved media and content validation, as well as the measurement of student responses and conceptual understanding. The findings indicate that the media is highly feasible, with a technical feasibility score of 93% and a content and objective feasibility score of 92%, and is considered highly practical based on student evaluations. Additionally, the majority of students achieved very good and good levels of conceptual understanding. In conclusion, the Articulate Storyline 3-based Play Mathematics media is a feasible, practical, and effective tool for mathematics learning, particularly in exploring mathematical concepts.